Crashworthiness of recycled carbon fiber composite sinusoidal structures at dynamic rates. (1st May 2023) - Barnett, Philip R.; Vigna, Lorenzo; Martínez-Collado, José L.; Calzolari, Andrea; Penumadu, Dayakar
Highlights: Recycled discontinuous carbon fiber composites offer high specific energy absorption at dynamic rates. Thermoplastic fiber-reinforced composites perform well at both static and dynamic crash rates at temperatures relevant to automotive operation. The embodied manufacturing energy of crashworthy recycled fiber composites is reduced without significantly impeding crashworthiness. Abstract: Fiber reinforced polymer composites are finding applications in the automotive space for structurally critical applications including crash management. The use of recycled carbon fiber reinforcement can greatly reduce carbon emissions. In this study, recycled carbon fiber composites were manufactured into a self-supporting geometry using three matrices: polyphenylene sulfide (PPS), acrylonitrile butadiene styrene (ABS), and a structural epoxy, and subsequently crushed between flat platens at dynamic rates ranging from 4.6 to 9.1 m s −1 at temperatures in a range of −40 °C to 80 °C. Load-displacement data was used to evaluate their specific energy absorption, crush efficiency, and steady-state crush stress. The energy absorption of the ABS composites was strongly sensitive to temperature, while the PPS composites exhibited strong crush efficiency dependence with both rate and temperature. The epoxy composites exhibited stable crush behavior at dynamic crush rates but exhibited a dramatic reduction in crush efficiency relative to quasi-static tests. The results of this study indicate that recycled fiber composites can achieve very high energy absorption levels (50–80 kJ kg −1 at room temperature) that make them an excellent alternative to more expensive and less environmentally friendly continuous virgin fiber laminates.